Five years of experience with biochemical cystic fibrosis newborn screening based on IRT/PAP in Germany. Issue 7 (23rd April 2015) - Sommerburg, Olaf; Hammermann, Jutta; Lindner, Martin; Stahl, Mirjam; Muckenthaler, Martina; Kohlmueller, Dirk; Happich, Margit; Kulozik, Andreas E.; Stopsack, Marina; Gahr, Manfred; Hoffmann, Georg F.; Mall, Marcus A.
Summary Background Evidence from recent studies suggests that IRT/PAP protocols may be successfully used as a purely biochemical newborn screening (NBS) for cystic fibrosis (CF) that does not require genetic screening. However, the experience with the performance of different IRT/PAP protocols remains limited. In this study, we evaluated the performance of IRT/PAP‐based CF‐NBS used in two German regions between 2008 and 2013 in a large cohort. Methods In both regions slightly different IRT/PAP protocols were used to screen newborns for CF. In contrast to the original IRT/PAP protocol published by Sarles et al., both German protocols contained an IRT‐dependent safety net strategy (CF‐NBS positive, if IRT≥99.9th percentile). Positive rating of the screening result led to confirmatory diagnostics using sweat chloride testing and clinical assessment. Findings A total of 328, 181 newborns were tested with IRT/PAP in Germany within 5 years. 639 of these newborns (0.19%) were tested positive, and 60 infants were diagnosed with CF leading to a sensitivity of 0.968 and a PPV (positive predictive value) of 0.097. Compared to IRT/DNA protocols, the PPV of IRT/PAP is lower, but PAP used as second tier test has the advantage of a lower detection rate of healthy carriers and CF patients with equivocal results. Conclusions Our results obtained in a large cohort of ∼330, 000 newborns support the use of a purely biochemical IRT/PAP protocol as an acceptable alternative when genetic CF‐NBS has to be avoided. Pediatr Pulmonol. 2015; 50:655–664. © 2015 Wiley Periodicals, Inc.